Adverse fetal outcomes and its associated factors in Ethiopia: a systematic review and meta-analysis - Gedefaw, Getnet (BMC Pediatr, 2020)
BACKGROUND: Despite the reduction of neonatal morbidity and mortality, is one of the third Sustainable Development Goal to end the death of children, the burden of the problem still the major challenge in Ethiopia. Globally, the most common causes of neonatal morbidity and mortality are adverse fetal outcomes (low birth weight, stillbirth, prematurity, congenital defect). Therefore this systematic review and meta-analysis aimed to estimate the pooled prevalence of adverse fetal outcomes and its associated factors in Ethiopia. METHOD: International databases (PubMed, Google scholar, web of science and science direct) were searched. Seventeen articles were included, among these, fourteen were cross-sectional and three of them were case-control studies. Publication bias was employed using a funnel plot and eggers test. The I(2) statistic was computed to check the heterogeneity of studies. Subgroup analysis was performed for the evidence of heterogeneity. RESULT: A total of 11,280 study participants were used to estimate the pooled prevalence of adverse fetal outcomes. The overall pooled prevalence of adverse fetal outcomes in Ethiopia was 26.88% (95% CI; 20.73–33.04). Low birth weight 10.06% (95% CI; 7.21–12.91) and prematurity 8.76% (95% CI; 5.4–12.11) were the most common adverse birth outcome at the national level. Rural in residency (AOR = 2.31; 95% CI: 1.64–3.24), lack of antenatal care follow up (AOR = 3.84; 95% CI: 2.76–5.35), pregnancy-induced hypertension (AOR = 7.27; 95% CI: 3.95–13.39), advanced maternal age ≥ 35(AOR = 2.72; 95% CI: 1.62–4.58, and having current complication of pregnancy (AOR = 4.98; 95% CI: 2.24–11.07) were the factors associated with adverse birth outcome. CONCLUSION: The pooled prevalence of adverse fetal outcomes in Ethiopia was high. Rural in residency, lack of antenatal care follow up, pregnancy-induced hypertension, advanced maternal age ≥ 35, and having current complications of pregnancy were the factors associated with adverse fetal outcomes. PROSPERO PROTOCOL REGISTRATION: CRD42020149163.